THE INFLUENCE OF WORK FACILITIES, OCCUPATIONAL SAFETY AND HEALTH ON THE WORK EFFECTIVENESS OF BREBES VILLAGE EMPLOYEES - Cromain, Hendrikus Putra; Wulandari Sutejo, Lusia (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
This research aims to determine the influence of work facilities, occupational safety and health on the work effectiveness of employees in Brebes Village, partially or simultaneously. The populace on this examine became all 15 Brebes Village employees. The sampling method uses a saturated sampling approach where the complete population is sampled. statistics series from dispensing questionnaires from respondents' answers. The type of this research is descriptive quantitative using multiple linear regression analysis in the SPSS 26 utility. primarily based at the outcomes of partial check analysis (t test) it shows that work facilities have a massive positive effect on worker work effectiveness as evidenced by means of the effects of tCount > tTable, particularly 2.225 > 1.782 . The effects of the partial check (t test) for occupational safety and health have a large high quality impact on worker work effectiveness as evidenced with the aid of the price of tCount > tTable, specifically 2.344 > 1.782. The outcomes of the simultaneous check (F test) show that work facilities, work safety and health together have a substantial high quality have an effect on on worker work effectiveness, that is verified by means of the cost of FCount > FTable, namely 17.424 > 3.810 on this study.